Origins of 1/f noise in nanostructure inclusion polymorphous silicon films - Wu Jiang; Wang Zhiming; Salamo Gregory; Ying Zhihua; Li Shibin; Jiang Yadong; Wu Zhiming; Li Wei (Nanoscale Research Letters, 2011)
Abstract In this article, we report that the origins of 1/f noise in pm-Si:H film resistors are inhomogeneity and defective structure. The results obtained are consistent with Hooge's formula, where the noise parameter, αH, is independent of doping ratio. The 1/f noise power spectral density and noise parameter αH are proportional to the squared value of temperature coefficient of resistance (TCR). The resistivity and TCR of pm-Si:H film resistor were obtained through linear current-voltage measurement. The 1/f noise, measured by a custom-built noise spectroscopy system, shows that the power spectral density is a function of both doping ratio and temperature.